Implantação eficiente de múltiplas coreografias de serviços em nuvens híbridas - Gomes, Raphael de Aquino (2017)
This thesis proposes a model-based approach to abstracting, simplifying, and automating cloud resource management decisions to deploy a set of service choreographies subject to non-functional constraints. Given a high-level description of service choreographies and related constraints, the approach autonomously performs resource estimation, selection, and allocation in a hybrid cloud environment with multiple cloud providers whilst decreases resource utilization costs and inter-services communication overhead. The main motivation for this work is because service choreographies are widely used for the development of solutions with complex needs, with service sharing among them. This scenario turns resource management a challenging task, mainly due to the different roles that a service assumes, the interference among constraints, and a large number of available resource types. This thesis also proposes an architecture that extends the approach with strategies to dynamic resource management to face constraint violations. This architecture was partially implemented in a prototype that was used in the proposed approach evaluation.